Patient and Surgeon Satisfaction Levels after Using an Acrylic, Hydrophobic, Monofocal IOL and the Malyugin Ring in Pseudoexfoliation Syndrome Patients - Andreas F. Borkenstein; Eva-Maria Borkenstein (Journal of Ophthalmology)
Purpose. The purpose of this prospective analysis was to evaluate the patient and surgeon satisfaction levels after using a fully preloaded acrylic, hydrophobic, monofocal “premium” IOL in pseudoexfoliation syndrome. Materials and Methods. 42 eyes of twenty-eight patients with progressed cataract formation and pseudoexfoliation syndrome (PXF) or pseudoexfoliation glaucoma and best corrected distance visual acuity (BCDVA) between 0.30–1.00 logMAR were enrolled. After a detailed preexamination, they underwent phacoemulsification and implantation of the acrylic, hydrophobic, heparin-coated, single-piece, monofocal intraocular lens (CT LUCIA 601P, Zeiss, Germany) with 360° square edge and ultraclear purity aspheric ZO optic. We evaluated the visual performance of the IOL and the patient satisfaction. We also evaluated the intraoperative handling of the injector and the behavior of the IOL in these complicated cases (PXF). Results. The BCDVA increased from mean 0.48 logMAR (range 0.30–1.00 logMAR) preoperatively to −0.05 ± 0.13 logMAR postoperatively. The mean IOL power was 23.5 D (range 16.5–27.5 D). The target refraction using the Haigis formula within ±0.5 D was reached by 92.9% (n=39) and by 100% (n=42) within 1.0 D of all cases, respectively. Patient satisfaction was very high, and no halos or glare were reported in any case. The fully preloaded injector system enabled an easy IOL preparation and safe implantation. Conclusion. Our results show that the implantation of the fully preloaded CT LUCIA 601P (Zeiss, Germany) is safe and enhances OR workflow in complicated cases as pseudoexfoliation. In these cases, an adapted approach (special preoperative, intraoperative, and postoperative regime) with considering possible complications is necessary to achieve best outcomes.